1996
DOI: 10.1002/j.1460-2075.1996.tb00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the duplicated CCAAT box region in gamma-globin gene regulation and hereditary persistence of fetal haemoglobin.

Abstract: Hereditary persistence of fetal haemoglobin (HPFH) is a clinically important condition in which a change in the developmental specificity of the gamma‐globin genes results in varying levels of expression of fetal haemoglobin in the adult. The condition is benign and can significantly alleviate the symptoms of thalassaemia or sickle cell anaemia when co‐inherited with these disorders. We have examined structure‐function relationships in the −117 HPFH gamma promoter by analysing the effect of mutating specific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
5

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 18 publications
1
57
0
5
Order By: Relevance
“…In addition, gel shift assays have shown that GATA-1 binds weakly to the duplicated CCAAT box region (3,15,21). A suggestion that GATA-1 binding to the duplicated CCAAT box region functions as ␥ gene repressor (3,21) was not supported by later experiments (29). It is possible that NF-Y and GATA-1 bind competitively to the duplicated CCAAT box region and that the mutation of the two CCAAT motifs, by severely impairing the binding of NF-Y, increases the probability of binding of GATA-1 to this region.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, gel shift assays have shown that GATA-1 binds weakly to the duplicated CCAAT box region (3,15,21). A suggestion that GATA-1 binding to the duplicated CCAAT box region functions as ␥ gene repressor (3,21) was not supported by later experiments (29). It is possible that NF-Y and GATA-1 bind competitively to the duplicated CCAAT box region and that the mutation of the two CCAAT motifs, by severely impairing the binding of NF-Y, increases the probability of binding of GATA-1 to this region.…”
Section: Discussionmentioning
confidence: 95%
“…Two more factors are known to influence the expression of the ␥-globin gene and may have a role in Hb switching. One is COUP-TFII (44), a retinoic acid orphan receptor that corresponds to the erythroid specific binding activity of NF-E3 (45,46). The protein binds to a consensus site that includes the ␥-globin CAAT element and may act as a repressor of the ␥-globin expression (47).…”
Section: Hb Switchingmentioning
confidence: 99%
“…In filamentous fungi, the CCAAT sequence is also shown to modulate the expression of many genes, such as the A. nidulans acetamidase gene (amdS) (Littlejohn and Hynes, 1992), the A. oryzae Taka-amylase A gene (taa) (Nagata et al, 1993), the A. nidulans penicillin biosynthesis gene (ipnA and aatA) , and the Neurospora crassa NADP-specific glutamate dehydrogenase gene (am) (Frederick and Kinsey, 1990) (Table 2). In higher eukaryotes, all kinds of promoters have the CCAAT sequence: developmentally controlled and tissue-specific genes (Berry et al, 1992;Ronchi et al, 1996), housekeeping and inducible genes (Marziali et al, 1997;Roy and Lee, 1995), and cell-cycle regulated genes (Mantovani, 1998).…”
Section: A Wide-domain Regulatory Factor Hap Complexmentioning
confidence: 99%